SOCIAL MEDIA AS AN EMOTIONAL OUTLET FOR WOMEN: AN ANALYSIS OF EMOTIONAL REGULATION PROCESSES FROM A MENTAL HEALTH PERSPECTIVE - Sumarna, Ajeng Fajarwati Sumarna (CV. Lafadz Jaya, 2024)
The role of social media in shaping emotional expression and mental health has become a critical area of study, especially concerning women. This research investigates how women utilize social media platforms as spaces for emotional regulation, analyzing the effects on mental health from an emotional regulation framework. Drawing from qualitative interviews and content analysis, this study examines the patterns through which women express, manage, and seek support for their emotions online. The findings reveal a dual impact of social media on women's mental health. While platforms provide a supportive space for self-expression, connection, and validation, they also present challenges, such as privacy concerns, exposure to negative feedback, and the risk of emotional fatigue due to constant social comparison. These challenges highlight a paradoxical relationship, where social media acts as both a tool for emotional resilience and a source of stress. This study contributes to an understanding of the complexities in digital emotional regulation, offering insights into how women navigate emotional well-being within a digital context. The findings underscore the importance of awareness around the positive and negative impacts of digital emotional spaces and offer implications for enhancing supportive online environments for mental health.